Knowledge Representation and Digital Scholarly Editions in Theory and Practice - Tanya Clement (Journal of the Text Encoding Initiative)
In Transition: Selected Poems by the Baroness Elsa von Freytag-Loringhoven is a publicly available scholarly edition of twelve unpublished poems written by Freytag-Loringhoven between 1923 and 1927. This edition provides access to a textual performance of her creative work in a digital environment. It is encoded using the Text Encoding Initiative’s (TEI) P5 Guidelines for critical apparatuses including parallel segmentation and location-referenced encoding. The encoded text is rendered into an interactive web interface using XSLT, CSS, and JavaScript available through the Versioning Machine (http://www.v-machine.org/). One aspect of textual performance theory I am exploring within In Transition concerns the social text network. The social text network these twelve texts always and already represent presupposes the notion of a constant circulation of networked social text systems. The network represented by In Transition is based primarily on issues of reception, materiality, and themes which engage and reflect the social nature of the text in the 1920s and now. This is to say two things: (1) that the concept of the network is not new with digital scholarly editions; and (2) that these networks in a digital edition foreground the situated 1920s history of these texts as well as the real-time, situated electronic reading environment. The argument of a digital edition like In Transition is formed as much by the underlying theory of text as it is by its content and the particular application or form it takes. This discussion employs the language of knowledge representation in computation (through terms like domain, ontology, and logic) in order to situate this scholarly edition within two existing frameworks: theories of knowledge representation in computation and theories of scholarly textual editing.